Changes in Corneal Densitometry in Patients with Fuchs Endothelial Dystrophy after Endothelial Keratoplasty. (1st February 2017) - Alnawaiseh, Maged; Rosentreter, André; Prokosch, Verena; Eveslage, Maria; Eter, Nicole; Zumhagen, Lars
ABSTRACT: Purpose : The aim of the study was to quantify corneal densitometry in patients with Fuchs endothelial dystrophy (FED) after endothelial keratoplasty. Materials and methods : We retrospectively reviewed the charts and anterior segment data of patients with FED before and after endothelial keratoplasty. Patients were examined using the Scheimpflug-based Oculus Pentacam corneal densitometry module. Densitometry parameters in different corneal layers and in different annuli were extracted and analyzed. Results : 27 eyes of 27 patients after endothelial keratoplasty (11 DSAEK, 16 DMEK) were included. After endothelial keratoplasty the total corneal light backscatter at total corneal thickness in the central cornea (0–2 mm annulus) was significantly lower than before (DSAEK: p = 0.026, DMEK: p = 0.001). In the entire group the total corneal light backscatter at total corneal thickness and at total diameter before surgery correlated with the postoperative values (Pearson correlation = 0.49, p = 0.01). The strongest correlation was found in the central layer in the DMEK group (Pearson correlation = 0.79, p < 0.001). Conclusions : Corneal densitometry is a useful, objective method for quantification of the outcome of posterior lamellar keratoplasty irrespective of visual acuity. There is a significant correlation between preoperative and postoperative corneal light backscatter values after endothelial keratoplasty, especially in the case of the DMEK procedure.